Analisis Strategi Harga Dan Produk Dalam Meningkatkan Kepuasan Konsumen Shopee - Nurul Hasanah; Yohana Tio Syarina Siringoringo; Harun Saputra Zebua; Christian Mora Sihombing; Ramadha Aditya Putra; Nela Permata Sari Lubis (Jurnal Keluarga Sehat Sejahtera, 2026)
The purpose of this study is to analyze the influence of price and product strategies on customer satisfaction in Shopee online business. Product and price strategies are now essential for drawing in and keeping consumers in Indonesia due to the growth of digital enterprises and the country's growing usage of marketplaces. This study reviewed several pertinent books, journals, and scientific publications over the previous five years using a qualitative approach and a library research method. Through the identification, comparison, and interpretation of several study findings pertaining to pricing strategy, product strategy, and customer happiness in online firms, data were evaluated utilizing a descriptive-analytical technique. The findings demonstrated that Shopee customer happiness is positively impacted by product quality, product variety, product conformance to description, and competitive price. Because it is simpler for customers to compare prices among suppliers on a single platform, pricing was found to have a greater effect than product. Additionally, client loyalty is boosted by incentives like free delivery, discounts, and flash sales. According to the study's findings, a good shopping experience and higher consumer satisfaction on the Shopee platform may be achieved by combining high-quality products with an appropriate price strategy.